2021
DOI: 10.3390/w13182489
|View full text |Cite
|
Sign up to set email alerts
|

Performance Assessment System to Wastewater Utilities Strategic Planning

Abstract: Urban water utilities face growing challenges in compliance with increasingly demanding legislation, tightening budgets, ageing personnel, decreasing infrastructure reliability, increasing operational costs, regulatory pressure, and climate change. Within this context, tracking the alignment of the performance with the mission and strategic objectives of the organization, based on reliable and up-to-date data, is of utmost importance to enable effective and continual improvement management. Organizational perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In line with the need to provide adequate service levels, a structured PAS for strategic infrastructure assessment management was developed by Alegre and Coelho (2012) and Alegre et al (2013). In addition, different PAS were developed for the diagnosis of water losses and energy inefficiencies in drinking water systems (Mamade et al, 2017), undue inflows and systems' functioning aspects in wastewater and stormwater systems (Almeida et al, 2017;Santos, 2021) and energy inefficiencies in urban water systems (Loureiro et al, 2020).…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…In line with the need to provide adequate service levels, a structured PAS for strategic infrastructure assessment management was developed by Alegre and Coelho (2012) and Alegre et al (2013). In addition, different PAS were developed for the diagnosis of water losses and energy inefficiencies in drinking water systems (Mamade et al, 2017), undue inflows and systems' functioning aspects in wastewater and stormwater systems (Almeida et al, 2017;Santos, 2021) and energy inefficiencies in urban water systems (Loureiro et al, 2020).…”
Section: Introduction and Reviewmentioning
confidence: 99%
“…Previous studies on strategic and tactical assessments of wastewater utilities provide the background for proceeding with this analysis, looking at the water, energy, and emissions nexus [27][28][29]. Results showed that service provision objectives are compromised by overflow discharges and surface flooding, even if not regularly quantified.…”
Section: Introductionmentioning
confidence: 99%
“…As proposed in[28]; 2 as proposed in[27]; 3 adapted from[28] (the reference values were adapted to the current study, in P11-P13, considering an impact factor associated with the electric consumption of 0.47 kgCO2 eq/kWh according to[30], for the Portuguese scope).…”
mentioning
confidence: 99%